2004
DOI: 10.1007/bf03403633
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette Smoking, Mental Health and Social Support

Abstract: Background:The prevalence of smoking is high in many Aboriginal Canadian communities; rates of 50% are not uncommon. Aboriginal Canadians suffer a severe burden of smoking-related disease. Research in other populations has linked depression and smoking. It is not known whether mental health or affective measures are related to smoking for any of Canada's First Nations, and this study sought to answer this question. Understanding relations between affect and smoking behaviour is requisite to mounting anti-smoki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
20
2

Year Published

2004
2004
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 49 publications
3
20
2
Order By: Relevance
“…The BSD has established concurrent and discriminant validity 19. Positive and negative affect were measured using the two 5-item scales of the Affect Balance Scale20 which have been used with other indigenous populations 21. Recent analysis of this measure confirmed its psychometric validity22 (in this study, negative affect balance scale α=0.54 and positive affect balance scale α=0.67).…”
Section: Methodssupporting
confidence: 51%
“…The BSD has established concurrent and discriminant validity 19. Positive and negative affect were measured using the two 5-item scales of the Affect Balance Scale20 which have been used with other indigenous populations 21. Recent analysis of this measure confirmed its psychometric validity22 (in this study, negative affect balance scale α=0.54 and positive affect balance scale α=0.67).…”
Section: Methodssupporting
confidence: 51%
“…Indeed, indigenous people are displaying rates of smoking often double the average of the broader population. [5][6][7][8] These patterns have emerged in the context of comprehensive tobacco policy environments. For example, low income people in developed countries are now most likely to start and maintain tobacco use despite increasing taxes and prices and widespread public health messaging and health knowledge about the dangers of smoking.…”
mentioning
confidence: 99%
“…A recent study from Canada found that, among especially marginalised populations, self mastery and social support were significantly lower among smokers compared to non-smokers. 18 In the present study we analyse the relationship between unemployment and smoking. We are also interested in examining the role of psychosocial factors as potential mediators for the relationship.…”
mentioning
confidence: 99%